2012
DOI: 10.1128/mcb.06619-11
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Remodeler SNF2L Suppresses Cell Proliferation and Migration and Attenuates Wnt Signaling

Abstract: ISWI is an evolutionarily conserved ATPase that catalyzes nucleosome remodeling in different macromolecular complexes. Two mammalian ISWI orthologs, SNF2H and SNF2L, are thought to have specialized functions despite their high sequence similarity. To date, the function of SNF2L in human cells has not been a focus of research. Newly established specific monoclonal antibodies and selective RNA interference protocols have now enabled a comprehensive characterization of loss-of-function phenotypes in human cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…PCTK3 , cyclin‐dependent kinase 18, also plays a role in the secretory pathway . SMARCA1 encodes an ATPase involved in nucleosome remodeling while RRM2 encodes a subunit of ribonucleotide reductase. We observed that expression of these genes was downregulated in hPSCs seeded at high density as compared to cells seeded at low density (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCTK3 , cyclin‐dependent kinase 18, also plays a role in the secretory pathway . SMARCA1 encodes an ATPase involved in nucleosome remodeling while RRM2 encodes a subunit of ribonucleotide reductase. We observed that expression of these genes was downregulated in hPSCs seeded at high density as compared to cells seeded at low density (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This would be consistent with our findings of increased TUNEL staining in Snf2h cKO-Nes mice at the onset of GNP expansion. Similarly, RNAi depletion in HeLa or U2OS cells results in increased apoptosis 24 h after SNF2H or ACF1 protein expression was strongly reduced3738. Nonetheless, several alternative explanations exist that could account for the decreased growth of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…In these follow-up studies, they observed that knockdown of SNF2LT or the full-length SNF2L gene resulted in similar cancer cell-specific phenotypes (Ye et al, 2012). Similar knockdown studies have shown that SNF2L is an essential regulator of the Wnt signaling pathway (Eckey et al, 2012). In these studies, in contradiction to previous SNF2L studies, SNF2L depletion results in increased proliferation and chemotaxis.…”
Section: A Review Of the Literature On Chromatin Remodeling And Camentioning
confidence: 54%